Serum cobalt concentrations remain at low levels at a minimum of 20 years following metal-on-metal total hip arthroplasty. Issue 3 (March 2020) - Waldstein, Wenzel; Koller, Ulrich; Springer, Bernhard; Kolbitsch, Paul; Brodner, Wolfram; Windhager, Reinhard; Lass, Richard
Abstract : Aims: Second-generation metal-on-metal (MoM) articulations in total hip arthroplasty (THA) were introduced in order to reduce wear-related complications. The current study reports on the serum cobalt levels and the clinical outcome at a minimum of 20 years following THA with a MoM (Metasul) or a ceramic-on-polyethylene (CoP) bearing. Methods: The present study provides an update of a previously published prospective randomized controlled study, evaluating the serum cobalt levels of a consecutive cohort of 100 patients following THA with a MoM or a CoP articulation. A total of 31 patients were available for clinical and radiological follow-up examination. After exclusion of 11 patients because of other cobalt-containing implants, 20 patients (MoM (n = 11); CoP (n = 9)) with a mean age of 69 years (42 to 97) were analyzed. Serum cobalt levels were compared to serum cobalt levels five years out of surgery. Results: The median cobalt concentration in the MoM group was 1.04 μg/l (interquartile range (IQR) 0.64 to 1.70) at a mean of 21 years (20 to 24) postoperatively and these values were similar (p = 0.799) to cobalt levels at five years. In the CoP control group, the median cobalt levels were below the detection limit (< 0.3 μg/l; median 0.15 μg/l, IQR 0.15 to 0.75) at 20 years. The mean Harris Hip Score was 91.4 points (61 to 100) in the MoM group and 92.8 points (63 to 100) in the CoP group. Conclusion: This study represents the longest follow-up series evaluating the serum cobalt levels after 28 mm head MoM bearing THA and shows that serum cobalt concentrations remain at low levels at a mean of 21 years (20 to 24) after implantation. Cite this article: Bone Joint Res. 2020;9(3):145–150.